Recent progress on formulations of hirudin - Zheng Bao; Xingyu Qi; Suling Zhu; Mao Zhang; Xinyue Liu; Peidong Chen; Li Zhang; Ting Geng; Fang-Fang Cheng (Pharmaceutical Science Advances)
Hirudin is an effective active ingredient derived from the salivary glands of leech. It is a small peptide molecule consisting of 65–66 amino acids and demonstrates a strong inhibitory effect on thrombin, providing beneficial anticoagulant and antithrombotic properties. However, as a biopharmaceutical peptide, it has some drawbacks such as easy degradation, short half-life, low bioavailability, and high risk of hemorrhage in clinical use. To overcome these challenges, various formulations were developed. In this work, a comprehensive review of research progress was provided in both traditional and novel hirudin formulations, spanning from lyophilized powders to biotechnology-based pharmaceuticals, covering various dosage forms to offer comprehensive references for field research. Firstly the advantages and limitations of conventional preparations were assessed such as freeze-dried powders, capsules, and injections. Then a detailed exploration of frontier strategies including nanotechnology-based delivery systems, transdermal formulations, and biotechnology-driven prodrug designs were conducted. This article aims to comprehensively analyze cutting-edge advancements in hirudin preparation research, providing updated information for relevant researchers by integrating traditional dosage optimization with breakthrough emerging technologies.